Structural characterization and biological activities of polysaccharide iron complex synthesized by plant polysaccharides: A review - Jing, Yongshuai; Zhang, Shilin; Li, Mingsong; Zhang, Ruijuan; Zhang, Hao; Zheng, Yuguang; Zhang, Danshen; Wu, Lanfang (Frontiers in Nutrition, 2022)
Iron deficiency anemia can lead to a variety of functional disorders, which is one of the highest incidence of nutrient deficiency diseases. The direct addition of iron to food will not only brings difficulties to the production of products, but also brings damages to human body. In recent years, studies at domestic and abroad have shown that polysaccharide iron complex (PIC) not only has a variety of biological activities of polysaccharide itself, but also has the function of supplementing iron, so it is a good iron supplement. With the advantages of good solubility, high iron content, low gastrointestinal irritation and high bioavailability, PIC is an effective iron supplement for iron deficiency anemia and has attracted more and more attention. In this paper, the different preparation methods, structural characterization, biological activities and clinical applications of PIC synthesized by natural polysaccharides from plant were reviewed, in order to provide theoretical basis for the development and application of PIC.